MADS-Box Transcription Factor ZtRlm1 Is Responsible for Virulence and Development of the Fungal Wheat Pathogen Zymoseptoria tritici - Mohammadi, Naser; Mehrabi, Rahim; Mirzadi Gohari, Amir; Roostaei, Mozaffar; Mohammadi Goltapeh, Ebrahim; Safaie, Naser; Kema, Gert H. J. (Frontiers in Microbiology, 2020)
Zymoseptoria tritici is one of the most economically destructive wheat diseases worldwide and is a model fungal plant pathogen within the ascomycetes. In this study, we functionally characterized the biological role of the ZtRlm1 gene encoding a MADS-box transcription factor (TF) in Z. tritici as these proteins play critical roles in the global gene regulation required for various developmental and physiological processes. Infection assays showed that ZtRlm1 mutants were attenuated in disease development as a 30% and 90% reduction in chloro-necrotic lesions and pycnidia formation, respectively, were observed in plants inoculated with ZtRlm1 mutant strains demonstrating that ZtRlm1 is a crucial factor playing a significant role in the late stage of infection corresponding with pycnidial formation. Expression analysis showed that ZtRlm1 is up-regulated during the early and late stages of infection, coinciding with pycnidial formation. In addition, microscopic analyses showed that branch intensity and biomass production were significantly reduced, indicating that impaired pycnidia formation is a result of impaired differentiation and biomass production in the ZtRlm1 mutants. Furthermore, melanization, a phenomenon required for fruiting body formation, was significantly hampered in ZtRlm1 mutants as they were not melanized under all tested temperature and media conditions. Overall, our data showed that impaired disease development of the ZtRlm1 mutants is mainly due to the significant impact of ZtRlm1 in different cellular processes, including differentiation, branching, fungal biomass production, and melanization, in which identification of downstream genes are of interest to increase our understanding of this pathosystem.